Direct Anterior Total Hip Arthroplasty - Galakatos, Gregory R. (Mo Med, 2018)
The direct anterior approach to the hip for total joint arthroplasty has been suggested to have several advantages compared to other popular approaches through its use of a natural intramuscular and intra-nervous interval. Recent emphasis on tissue sparing and minimally invasive outpatient joint replacements has given rise to a significant increase in the utilization of direct anterior total hip arthroplasty (DAA). Proponents of this approach cite improved recovery times, lower pain levels, improved patient satisfaction as well as improved accuracy on both implant placement/alignment and leg length restoration. A number of variations of the procedure have been described and many authors have published their experiences and technical keys to successfully accomplishing this procedure. Described techniques have been performed using specifically designed instruments and specific fracture tables and intra-operative flouroscopy, however this approach may be performed using a regular table with standard arthroplasty tools with alternative patient positioning and without intraoperative imaging. This review summarizes several aspects of the direct anterior approach for total hip arthroplasty and its comparison to other popular approaches to modern hip replacement.